2020
DOI: 10.1016/j.virol.2019.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Porcine deltacoronavirus (PDCoV) modulates calcium influx to favor viral replication

Abstract: A B S T R A C TIonic calcium (Ca 2+ ) is a versatile intracellular second messenger that plays important roles in cellular physiological and pathological processes. Porcine deltacoronavirus (PDCoV) is an emerging enteropathogenic coronavirus that causes serious vomiting and diarrhea in suckling piglets. In this study, the role of Ca 2+ to PDCoV infection was investigated. PDCoV infection was found to upregulate intracellular Ca 2+ concentrations of IPI-2I cells. Chelating extracellular Ca 2+ by EGTA inhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 61 publications
2
30
0
Order By: Relevance
“…These findings open up the possibility to find dual-action steroid-remdesivir combinations that have antiviral effects early in the infection and exert immunomodulatory effects, as achieved with dexamethasone, later. Synergy with remdesivir was also observed for compounds modulating calcium channel and proton pump activity, consistent with well-established modulation and exploitation of host cell calcium signaling during infection 30,31,45 . We identified as synergistic with remdesivir the generic calcium-channel blockers nimodipine and nifedipine which are widely used as anti-hypertensives and have an excellent safety profile 36 .…”
Section: Discussionsupporting
confidence: 81%
“…These findings open up the possibility to find dual-action steroid-remdesivir combinations that have antiviral effects early in the infection and exert immunomodulatory effects, as achieved with dexamethasone, later. Synergy with remdesivir was also observed for compounds modulating calcium channel and proton pump activity, consistent with well-established modulation and exploitation of host cell calcium signaling during infection 30,31,45 . We identified as synergistic with remdesivir the generic calcium-channel blockers nimodipine and nifedipine which are widely used as anti-hypertensives and have an excellent safety profile 36 .…”
Section: Discussionsupporting
confidence: 81%
“…17,18 While porcine deltacoronavirus (PDCoV) is an emerging enteropathogenic coronavirus that causes serious vomiting and diarrhoea in suckling piglets, a recent study reported that PDCoV modulates calcium influx to favour viral replication. 19 In this study, treatment with Ca 2+ channel blockers, particularly the L-type CCB diltiazem hydrochloride, was shown to inhibit PDCoV infection significantly. Very recently, a retrospective clinical investigation of patients with COVID-19 patients revealed that the CCB amlodipine besylate administration was associated with reduced fatality rate of patients with hypertension.…”
Section: Prospects Of Researching On Calcium Channel Drug Targets Inmentioning
confidence: 76%
“…It is possible that the activation of these GABA A -Rs leads to Cl - efflux, which would act to limit Ca 2+ influx in these epithelial cells. Because many viruses, including coronaviruses, elevate intracellular Ca 2+ concentrations in order to enhance viral replication (22, 23), the activation of GABA A -Rs may have limited MHV-1 replication, a possibility that we are currently investigating.…”
Section: Resultsmentioning
confidence: 99%